Evaluación de la infección por Babesia spp. en garrapatas Rhipicephalus (Boophilus) microplus y la infestación en bovinos de 3 a 9 meses de edad en 9 hatos ganaderos del Magdalena medio Colombiano (2012)
ABSTRACT: Bovine babesiosis is an infection caused by the genus Babesia hemoparasite, which is transmitted by ticks Rhipicephalus (Boophilus) microplus. In the dynamics of parasite transmission different factors like geographic, environmental and epidemiological are needed to comprehension of dynamic transmission and to design appropriate control strategies. Objective To describe the degree of infestation by ticks Rhipicephalus (Boophilus) microplus and Babesia spp. in the vectors captured in cattle between the three and nine months of age, from nine herds from Colombian Middle Magdalena. Materials and methods We carried out a descriptive study with a convenience sample; the number of calves sampled was a total of 237.770 ticks were incubated for seven days at room temperature with relative humidity between 80%-90%, for subsequent analysis of their hemolymph by optical microscopy. Results The degree of infestation of the total area was 3.2 ticks per calf. The calves of six to seven months showed the highest degree of infestation with 4.7 ticks per calf. The total percentage of positive ticks by identification of parasitic forms of Babesia spp. was 9.1%. We found a positive correlation between the frequency of bathing ticks and parasite load (Rho: 0.168 and p = 0.010). Finally correlation was obtained between the parasite load and the type of farming p = 0.04. Conclusions Analytical studies are needed to deep into the relationship between entomological and parasitological and vector control strategies.